Simulation and Experimental Investigation of Performance and Flow Behavior for Steam Ejector Refrigeration System (Journal of Engineering, 2023)
The ejector refrigeration system is a desirable choice to reduce energy consumption. A Computational Fluid Dynamics CFD simulation using the ANSYS package was performed to investigate the flow inside the ejector and determine the performance of a small-scale steam ejector. The experimental results showed that at the nozzle throat diameter of 2.6 mm and the evaporator temperature of 10oC, increasing boiler temperature from 110oC to 140oC decreases the entrainment ratio by 66.25%. At the boiler temperature of 120oC, increasing the evaporator temperature from 7.5 to 15 oC increases the entrainment ratio by 65.57%. While at the boiler temperature of 120oC and the evaporator temperature of 10oC, increasing the nozzle throat diameter from 2.4 to 2.8 mm decreases the entrainment ratio by 40%. The numerical results showed that reducing the condenser back pressure or increasing the primary fluid temperature, secondary fluid temperature, and nozzle throat diameter moves the second shock waves in the downstream direction. It could be concluded that the second shock series position detects the ejector operation mode. The ejector runs in critical mode if the second shock series position is close to the diffuser. In contrast, if the second shock series position moves toward the upstream, the ejector runs in subcritical mode.